2018
DOI: 10.1111/sms.13240
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of balance training‐induced improvement in soccer‐specific skills in U11 soccer players

Abstract: The present study aimed to determine the role of balance training improving technical soccer skills in young players. Two U11 soccer teams were randomly assigned one to either balance training (BT; n = 22) or control group (Ctrl; n = 21). At the end of their habitual soccer training (identical in BT and Ctrl), BT underwent additional balance training for 12 weeks (3 sessions/week, 20 minutes per session), while Ctrl had a 20-minute scrimmage. Before and after the intervention, BT and Ctrl underwent two soccer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
(91 reference statements)
1
10
0
Order By: Relevance
“…Both of our balance training models followed for six weeks positively affected the chest passing accuracy of the athletes. The results of the present study support the concept that balance training, which has been examined in a limited number of studies, [1,11,49] are effective training models for improving sport-specific skills. In a study performed on male amateur basketball players, Kostopoulos et al [1] found that 12-weeks of balance training increased the passing accuracy rates by 14.92%.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Both of our balance training models followed for six weeks positively affected the chest passing accuracy of the athletes. The results of the present study support the concept that balance training, which has been examined in a limited number of studies, [1,11,49] are effective training models for improving sport-specific skills. In a study performed on male amateur basketball players, Kostopoulos et al [1] found that 12-weeks of balance training increased the passing accuracy rates by 14.92%.…”
Section: Discussionsupporting
confidence: 85%
“…The results of this study are similar to those of the study by Evangelos et al [11] who found that ten-week balance training performed on unstable surfaces improved certain technical skills in amateur footballers such as long passing (30%), short passing (27.56%) and ball control (48.73%). In addition, the increase in the chest passing ac-curacy rate of our young basketball players can be explained by the improvement on performance of balance in lower extremities while performing shooting and passing, which provide better body stabilization [49].…”
Section: Discussionmentioning
confidence: 99%
“…where x i is the detected value, r is the expected value that corresponds to the reference axis, and n is the total number of detected values. The TSI has already been demonstrated to be a valid index of the dynamic postural control ( Cè et al, 2018 ). In the DT conditions, the cognitive involvement in the two different postural tasks was assessed by considering the number of correct answers given by each participant.…”
Section: Methodsmentioning
confidence: 99%
“…Although the accuracy of the throws revealed a slight positive correlation with mean CoP velocity magnitude (players with better throw accuracy moved faster during the balance task), there was a negative correlation between the ball speed and bivariate variable error in experts ( Caballero et al, 2020 ). Nevertheless, low-to-moderate correlations between unipedal balance ability and the players’ technical level suggest that some technical soccer skills improve more after balance than typical soccer training ( Cè et al, 2018 ). This discrepancy in findings may be mainly ascribed to the degree of physical development of a particular group of athletes or their exposure to sport-specific tasks.…”
Section: Resultsmentioning
confidence: 99%